Evaluasi Usability dan Perbaikan Desain Antarmuka Pengguna Aplikasi Situs Berita Kontan menggunakan Pengujian Usability - Heru Purnomo; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Kontan is an economic, business and investment news portal. Not only presenting news and information, cash also presents macroeconomic data, sectoral, to stock market and financial data accurately, completely, and continuously updated, from trusted sources. Apart from being on the website, Cash also has an application on cellular phones. But in fact this application still gets a low rating in the Playstore and there are also some unfavorable reviews from users. The review can be categorized into errors in the Usability aspect, namely Learnability, efficiency, errors, and also Satisfaction. Then an evaluation is carried out to find out what problems are obtained from testing and direct observation to users of the Cash application. There are 4 problems that are included in the usability aspect. Then recommendations for interface improvements are made in order to increase the value from the usability aspect. Then a second evaluation was carried out using the same method as in the first evaluation, in order to find out the comparison between the first test and the second test. There was an increase in the learnability aspect by 4%, in the efficiency aspect there was an increase of 0.948, in the errors aspect there was a decrease of 0.53%, and also in the satisfaction aspect there was an increase of 10,583.